Perdagangan Pakaian Bekas Dalam Perspektif Perundang-Undangan Di Indonesia: Berkah Atau Musibah - Moammar Khadafi; Otih Handayani; Widya Romasindah Aidy (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The proliferation of imported used clothing trade is due to clothes sold having foreign brands at cheap prices so that people who want to stay fashionable prefer imported used clothes because they are considered more affordable. The Clinical Pathology Laboratory of Muhammadiyah University Surabaya stated that used clothing samples contained mold or yeast fungi, Staphylococcus aureus bacteria, Escherichia coli bacteria and HPV (Human Papilloma Virus). This study aims to investigate the regulations regarding the trade of secondhand clothing in Indonesia and explore the legal protection provided for consumers of secondhand clothing in the country. The study employed a normative juridical legal research method, utilizing both the statute approach and conceptual approach. It drew upon legal materials such as Law Number 8 of 1999, Law Number 36 of 2009, Law Number 7 of 2014, and Minister of Trade Regulation No. 18 of 2021. The initial finding of the research was that the importation of secondhand clothing in Indonesia has been prohibited under Minister of Trade Regulation No. 18 of 2021, Article 2, paragraph (3), while local secondhand clothing businesses are permitted based on the Indonesian Business Field Standard Classification (KBLI) with code 47742. Secondly, legal protection for secondhand clothing consumers in Indonesia has been regulated in Law Number 8 of 1999. One of the consumer rights that needs to be fulfilled in consumer protection is the right to compensation for losses suffered by consumers based on Article 4 number 8, Article 7 letter f, and Article 19 paragraph (1).